2020
DOI: 10.3389/fimmu.2020.588682
|View full text |Cite
|
Sign up to set email alerts
|

The Role of GITR/GITRL Interaction in Autoimmune Diseases

Abstract: Glucocorticoid-induced TNFR-related protein (GITR) is a member of the TNFR superfamily which is expressed in various cells, including T cells, natural killer cells and some myeloid cells. GITR is activated by its ligand, GITRL, mainly expressed on antigen presenting cells and endothelial cells. It has been acknowledged that the engagement of GITR can modulate both innate and adaptive immune responses. Accumulated evidence suggests GITR/GITRL interaction is involved in the pathogenesis of tumor, inflammation an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
39
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(43 citation statements)
references
References 64 publications
4
39
0
Order By: Relevance
“…Moreover, the CD137/CD137L interaction not only constitutes a costimulatory signal triggering the expansion of the CD4 + and CD8 + T cells, but also amplifies the inflammatory responses mediated by NK cells [ 61 ]. Our results also showed that MIM tends to increase the expression of GITRL on the HUVEC surface ( Figure 5 ), which may potentially facilitate GITR/GITRL signaling and thus result in T cell activation and proliferation [ 62 ]. Indeed, numerous studies using suboptimal preprimed anti-CD3 stimulated T cells reported the role of the GITR/GITRL axis as a costimulation signal for the T cells [ 63 ].…”
Section: Discussionmentioning
confidence: 81%
“…Moreover, the CD137/CD137L interaction not only constitutes a costimulatory signal triggering the expansion of the CD4 + and CD8 + T cells, but also amplifies the inflammatory responses mediated by NK cells [ 61 ]. Our results also showed that MIM tends to increase the expression of GITRL on the HUVEC surface ( Figure 5 ), which may potentially facilitate GITR/GITRL signaling and thus result in T cell activation and proliferation [ 62 ]. Indeed, numerous studies using suboptimal preprimed anti-CD3 stimulated T cells reported the role of the GITR/GITRL axis as a costimulation signal for the T cells [ 63 ].…”
Section: Discussionmentioning
confidence: 81%
“…(Supplementary Figure 1 ). The elevated GITRL or IL-4 have been thoroughly studied in RA and associated with disease severity linked to Th17-cell activation or autoantibody induction, respectively [ 16 , 17 ]. However, their association with the increased concentration with PYY (3-36) needs further mechanistic studies to explain.…”
Section: Resultsmentioning
confidence: 99%
“…GITR is a member of the tumor necrosis factor receptor (TNFR) family highly expressed on T regulatory (Treg) cells and present on effector T lymphocytes, natural killer cells, and neutrophils [ 63 , 64 ]. GITR is activated by its ligand, GITRL, mainly expressed on antigen-presenting and endothelial cells [ 65 ]. GITR activation on effector T cells generates a positive costimulatory signal and promotes T cell activation and proliferation; however, the activation of GITR on Treg cells abolishes their suppressive function in cancer settings [ 66 ].…”
Section: Metabolic Effects Of Stimulatory Immune Checkpoint Protein Activation On Immune Cellsmentioning
confidence: 99%